Egyptian Goose Alopochen aegyptiaca: an introduced species spreading in and from the Netherlands - Gyimesi, Abel; Lensink, Rob (Wildfowl, 2012)
The Egyptian Goose Alopochen aegyptiaca was introduced as an ornamental species to parks in the Netherlands during the 20th century because of its exotic plumage. Escaped birds started to breed in the wild in 1967, and the species has now colonised most of the country. From the 1980s onwards the birds spread further to Germany, then to Denmark, while escapes from parks in Brussels established viable populations there and in France. This study summarises the latest available information on the numbers and distribution of free-living Egyptian Geese in the Netherlands and Europe. The population dynamics of the species were analysed to provide a better understanding of the development of the Dutch population over the past 40+ years, with special attention paid to the effects of culling, natural winter mortality and possible habitat preferences. Numbers breeding in the Netherlands were estimated at c. 10,000 pairs in 2010, and the total population at c. 45,000 individuals in winter 2010/11. Both breeding and non-breeding numbers increased exponentially (by 28% annually) from the establishment in the wild until 1999. However, the rate of increase has slowed in the last ten years, likely due to saturation of available breeding sites and an increase in culling activity. Within-season mortality in severe winters exceeded that during mild winters. The success of the Egyptian Goose in the Netherlands can likely be attributed to the abundance of freshwater areas available close to grasslands with few trees. Extrapolation up to 2010 of trends observed in Belgium and Germany until 2005 and 2006, respectively, suggests that these breeding populations together exceed 16,000 pairs, bringing the total numbers breeding in northwest Europe (including pairs in Britain, France and Denmark) to > 26,000 pairs.